Awareness of the Employment Crisis on @CNNIndonesia Among Islamic Broadcasting Students at the State Islamic University of North Sumatra - Fathurrahman, Aulia (Talenta Publisher, 2025)
Society has experienced rapid development in the fields of health, technology, and social life. The continuously evolving digital era has transformed various aspects of social life, particularly in the ways people communicate, access information, and develop social awareness. Mass media plays an important role as a medium of interaction and information dissemination within society, especially among Millennials and Generation Z, who are recognized as digital natives. This study aims to analyze the responses of students of the Islamic Broadcasting Communication (KPI) Study Program at UINSU toward the issue of the employment crisis in Indonesia, as well as to examine the influence of social media news coverage on their awareness. This study uses a descriptive qualitative approach with a case study method. The research subjects were KPI UINSU students from the 2022 cohort who had accessed employment-related news through the Instagram account @cnnindonesia. The findings indicate that news about the difficulty of obtaining employment uploaded by the Instagram account @cnnindonesia was perceived as relevant to the social realities faced by society, particularly young people. The limited availability of job opportunities has become a shared source of concern, especially for graduates who have not yet obtained employment opportunities. Nevertheless, some informants considered that the information presented was not significantly different from other media and therefore did not have a specific influence on their patterns of thought or actions.